Answer:
B. -1
Explanation:
STEP 1: Simplify 3x+2(x−9).
![5x-18=8x+x-14](https://img.qammunity.org/2021/formulas/mathematics/high-school/u8kbr7my6yhdyqq9cd8ef25go009c5e922.png)
STEP 2: Add 8x and x.
![5x-18=9x=-14](https://img.qammunity.org/2021/formulas/mathematics/high-school/emr22ifkl8v7xja2p6xd9puz9b86rk1clx.png)
STEP 3: Move all terms containing x to the left side of the equation.
![-4x-18=-14](https://img.qammunity.org/2021/formulas/mathematics/high-school/l3gn7edz538uy4918v60j81jrk2mxi2266.png)
STEP 3: Move all terms not containing x to the right side of the equation.
![-4x=4](https://img.qammunity.org/2021/formulas/mathematics/college/sphpdbma0u0m0q9ngeea7a98osloxk2sx7.png)
STEP 4: Divide each term by −4 and simplify.
![x=-1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/r09d2j03o35wlqb201n202kkqkmlb1vt4x.png)